Miniaturized methane detection system based on photoacoustic spectroscopy. Issue 5 (3rd January 2023) - Ye, Weilin; He, Linfeng; Xia, Zikun; Liu, Weihao; Huang, Yifei; Lin, Yiwen
Abstract: As an important means of trace gas detection, photoacoustic spectroscopy mainly detects gas concentration indirectly through the thermal effect of light. Methane detection system based on photoacoustic spectrum has great application prospect in environmental pollution detection and industrial production. As a container for loading methane, the shape and quality of the photoacoustic cell will have a huge impact on the final detection results. To improve the operability of the photoacoustic spectrum technology in practical application, this system improves the traditional photoacoustic cell. The integrated micro photoacoustic cell designed with 3D printing technology has a volume of 9 cm 3 and a theoretical resonance frequency of 11 000 Hz. Based on LabVIEW platform, a frequency sweep program and a concentration acquisition program were set up in the experiment. The frequency sweep experiment was carried out in an environment filled with methane in the photoacoustic cell. Based on the theoretical knowledge of photoacoustic spectroscopy, it can be known that the sound pressure detected by microphones is proportional to the concentration of methane in the photoacoustic cell. Methane with gradient concentration is passed into the photoacoustic cell for concentration calibration experiment, and the second harmonic peak detected at different concentrations is linearly fitted, and the line R 2 = 0.99919. By calculating Allan variance, it can be obtained that the minimum detection of the system can reach 6.89 ppm when the integration time is 49 s.